Evaluation of the effect of UGT1A1 polymorphisms on the pharmacokinetics of oral and long-acting injectable cabotegravir. (3rd May 2020) - Patel, Parul; Xue, Zhengyu; King, Karen S; Parham, Laura; Ford, Susan; Lou, Yu; Bakshi, Kalpana K; Sutton, Kenneth; Margolis, David; Hughes, Arlene R; Spreen, William R
Abstract: Background: Cabotegravir is an HIV integrase inhibitor in clinical development with both oral and long-acting (LA) injectable formulations. Cabotegravir is primarily metabolized by uridine 5′-diphospho-glucuronosyltransferase (UGT) 1A1, a known polymorphic enzyme with functional variants that can affect drug metabolism and exposure. Objectives: To investigate the pharmacogenetic effects of the reduced-function alleles UGT1A1 *6, UGT1A1 *28 and/or UGT1A1 *37 on steady-state pharmacokinetics (PK) and safety of oral cabotegravir (30 mg/day) and intramuscular cabotegravir LA (400 mg every 4 weeks or 600 mg every 8 weeks). Methods: Plasma cabotegravir PK was assessed in 346 UGT-genotyped participants with and without UGT1A1 functional variants across six studies (four Phase I and two Phase II) of oral cabotegravir, including 215 HIV-infected participants who received oral cabotegravir followed by cabotegravir LA. Changes from baseline in total bilirubin and ALT were assessed in one study (LATTE; NCT01641809). Results: Statistically significant ( P <  0.05) associations were observed between UGT1A1 genotype and plasma cabotegravir PK parameters, with 28%–50% increases following oral cabotegravir [plasma cabotegravir concentration at the end of the dosing interval ( C tau ), 1.50-fold; AUCtau, 1.41-fold; and C max, 1.28-fold] and 16%–24% increases following cabotegravir LA administration (48 week C tau, 1.24-fold; AUCtau, 1.16-fold; and C max, 1.18-fold) among those with low-versus-normal genetically predicted UGT1A1 activity. A statistically significant ( P <  10 −5 ) association between predicted UGT1A1 activity and maximum change in total bilirubin was also observed (2.45-fold asymptomatic increase for low versus normal) without a corresponding change in ALT. Conclusions: This modest increase in oral and parenteral cabotegravir exposure associated with a reduced function of UGT1A1 is not considered clinically relevant based on accumulated safety data; no dose adjustment is required.